SIFAT FISIK DAN ORGANOLEPTIK BERAS TIRUAN DARI MOCAF DAN TEPUNG JAGUNG DENGAN TEPUNG KETAN SEBAGAI BAHAN PENGIKAT - Triana Lindriati; . Djumarti; Lila Ismawati (Faculty of Agricultural Technology, University of Jember, 2014)
Indonesian is the greatest consumer of rice in the world. Their dependence on rice would bother national food security. The availability of artificial rice made from local materials is expected to overcome food security problem. Cassava and corn flour with glutinous rice flour addition as binding agent expected could produce good properties of artificial rice. This research used Modified Cassava Flour (MOCAF) to replace cassava flour. The experiment divided two levels and every level used factorial design with one factor. There were two levels which glutinous rice flour addition was factor in the first level and MOCAF and corn flour composition was factor in the second level. The best values of physical characteristic in the first level are 0% of glutinous rice flour addition with swelling power 94,16%, rehydrating power 73,73%, lightness 84,59, and chrome 28,14, also 20% of glutinous rice flour addition with dispersed material value 5,60%. Whereas, the best sensory evaluation is 0% of glutinous rice flour with whole hedonic score 4,02. The glutinous rice flour addition would reduce the presentage of dispersed material and reduce score of sensory evaluation. In the second level, the best values of swelling power is 118,57%at 40% of MOCAF, dispersed material is 3,60%at 100% of MOCAF. Whereas the best value of rehydrating power is 77,43% at 0% of MOCAF, lightness 87,16%, and chrome 27,24. The best value of sensory evaluation is 0% of MOCAF with score 4,68. Increasing of MOCAF would reduce dispersed material and reduce score of sensory evaluation.Keywords: artificial rice,starch gelatinyzation, mocaf, glutinous rice flour